(untitled) (Journal of Human Sciences, 2022)
This The crime of an influence peddling considers to be one of the most serious crimes that interrupt the functioning of the civil service and question its integrity. This study tried to highlight the protection mechanisms at the legal and institutional levels to confront this crime in Libya. Despite the efforts made to criminalize most behaviors of abusing or exploiting power, (which culminated in the Libyan legislator’s ratification of the United Nations Convention against Corruption more than fifteen years ago), Libya has remained rank at the lowest levels of the international transparency index. Based on the abovementioned, it became clearer that the regulator was not fully successful to some extent in the legal policy that adopted in combating the crime of influence peddling and averting its danger to the administration and public function, whether in terms of criminalization or punishment, or in terms of the structural mechanisms of the national institutions entrusted with it. Combating all modes of behavior that lead to the crime of influence peddling, begins with the request, accepting an offer, or a promising to accept it by the offender as a public servant. Considering that the crime of influence peddling is among the crimes of those related to occupational crimes. It concluded that despite the adoption by the criminal regulator a broad concept of the public servant (the abuser of power), it ignored somehow to criminalize the influence peddling by a private, a foreign and international employee who work in Libya. Like its exclusion to criminalize the use of power to obtain profit or spoils from any kind of administrations or authorities whether national or foreign.